Pengaruh Kepemimpinan terhadap Kinerja Karyawan Pada PT. Akebono Brake Astra Indonesia - Nurlela, Siti; Amin, Mustangin (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Leadership on Employee Performance at PT. Akebono Brake Astra Indonesia, Management Study Program, Faculty of Economics and Business, Jayabaya University, under the guidance of Dr. Mustangin Amin, SE., MM. This research aims to find out whether there is an influence between Leadership (XI) on Employee Performance (Y) of PT employees. Akebono Brake Astra Indonesia. The method used in this research is a quantitative method with data collection techniques through questionnaires. The sample used in this research was 53 respondents. The data analysis techniques in this research are validity test, reliability test, correlation coefficient analysis, simple linear regression analysis, t test, and determination correlation analysis using the SPSS 25 program. The research results show that leadership has a positive and significant effect on employee job satisfaction at PT. Akebono Brake Astra Indonesia, where the significant value resulting from processing the t test is 0.000 < 0.05, and the calculated t value is 3.894 > t table 2.008, then Ho is rejected and Ha is accepted, meaning that partially there is a significant influence between leadership variables on employee performance . The results of the coefficient of determination show an R square value of 0.214 or 21.4%, which means that the influence of leadership on employee performance is only 21.4%, while the remaining 78.6% is influenced by other factors not found in this research. Suggestions in this research for PT. Akebono Brake Astra Indonesia is a company that needs to pay more attention to the health of its employees, and companies need to supervise employees in completing work. Keywords: Employee Performance and Leadership.